2017
DOI: 10.3390/nu9040317
|View full text |Cite
|
Sign up to set email alerts
|

South Asian Ethnicity Is Related to the Highest Risk of Vitamin B12 Deficiency in Pregnant Canadian Women

Abstract: Vitamin B12 (B12) adequacy during pregnancy is crucial for maternal health and optimal fetal development; however, suboptimal B12 status has been reported in pregnant Canadian women. Methylmalonic acid (MMA) is a sensitive indicator of B12 status. Since few studies have measured MMA during pregnancy in Canadian women, the objective of this study was to evaluate B12 status in pregnant women living in Metro Vancouver, using both plasma total B12 and MMA. We recruited a convenience sample of 320 pregnant women be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
1
10
0
1
Order By: Relevance
“…Pre-pregnancy BMI was the strongest independent predictor of plasma total B12 concentration. One limitation of this data was the absence of a dietary assessment to quantify B12 intake, as this specific population promoted vegetarianism [69]. A study conducted in small sample of pregnant Indian women showed that hyperhomocystinemia leads to global DNA hypermethylation in vegetarian population due to low dietary intake of vitamin B-12 during pregnancy and that this could predispose to cardiovascular risk and obesity [70].…”
Section: Reviewmentioning
confidence: 99%
“…Pre-pregnancy BMI was the strongest independent predictor of plasma total B12 concentration. One limitation of this data was the absence of a dietary assessment to quantify B12 intake, as this specific population promoted vegetarianism [69]. A study conducted in small sample of pregnant Indian women showed that hyperhomocystinemia leads to global DNA hypermethylation in vegetarian population due to low dietary intake of vitamin B-12 during pregnancy and that this could predispose to cardiovascular risk and obesity [70].…”
Section: Reviewmentioning
confidence: 99%
“…The prevalence of B 12 deficiency, defined as serum total B 12 concentration <148 pmol/l, among reproductive-aged and pregnant women in Canada (25)(26)(27)(28)(29)(30) and the UK (31) was reported to range between 5 and 40 %. A recent cross-sectional study in pregnant women (20-35 weeks of gestation) residing in Vancouver, Canada, in which 18 % of the total sample had a total B 12 concentration <148 pmol/l, revealed a markedly higher prevalence among women whose self-identified ethnicity was South Asian (61•5 % (n 16/26)) compared with European (16 % (n 24/150)) (30) . Taken together, B 12 status Abbreviations: B 12 , vitamin B 12 ; holoTC, holotranscobalamin; MCA, 2-methylcitric acid; MMA, methylmalonic acid; tHcy, homocysteine.…”
mentioning
confidence: 99%
“…Logistic challenges and cultural barriers have been identified limiting health research in South Asians ( 24 ) . The prevalence of B 12 deficiency, defined as serum total B 12 concentration<148 pmol/l, among reproductive-aged and pregnant women in Canada ( 25 30 ) and the UK ( 31 ) was reported to range between 5 and 40 %. A recent cross-sectional study in pregnant women (20–35 weeks of gestation) residing in Vancouver, Canada, in which 18 % of the total sample had a total B 12 concentration<148 pmol/l, revealed a markedly higher prevalence among women whose self-identified ethnicity was South Asian (61·5 % ( n 16/26)) compared with European (16 % ( n 24/150)) ( 30 ) .…”
mentioning
confidence: 99%
“…In late pregnancy, i.e. in second or third trimester, pregnant women of South Asian ethnicity had the highest risk of B 12 deficiency compared with women of other ethnicities ( 57 ) . Underlying causes may be differences in dietary B 12 intake and supplement use related to cultural habits and traditions, potentially higher prevalence of vegetarianism, and/or higher prevalence of genetic variants related to lower serum total B 12 concentrations ( 58 ) .…”
Section: Influencing Factors On Biomarker Variability and Cut-offsmentioning
confidence: 99%